Asset Utilization and Company Performance - Christian Herdinata (UNUSA Press, 2019)
This study examines the expropriation that occurs in asset utilization due to tunneling. This study aims to examine the effect of asset utilization on company performance. This study used a sample of 130 companies in Indonesia to examine the effect of asset utilization on company performance. This research uses simultaneous equation model with Three-Stage Least Square tech- nique. The results showed that asset utilization has a positive and significant effect on company performance. The result of the research shows that asset utilization which is managed and well controlled has influence to improve company performance.